2013
DOI: 10.1139/cjz-2013-0068
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the endangered Butler’s Gartersnake (Thamnophis butleri): does the Short-headed Gartersnake (Thamnophis brachystoma) exist in Canada?

Abstract: Understanding population genetic structure is fundamental to conservation of endangered species. It is particularly important when working with species that are morphologically conserved because strong genetic divisions could represent cryptic species. Butler's Gartersnake (Thamnophis butleri (Cope, 1889)) is an endangered species in Canada, having a fragmented distribution and being restricted to southwestern Ontario. Furthermore, it is difficult to distinguish morphologically from a closely related species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
1
1
1
Order By: Relevance
“…The most coherent interpretation of our analyses for Thamnophis butleri is that there are distinct four genetic clusters. The genetic structure that we delineated for Thamnophis butleri supportsNoble et al (2013), who also found geographically delineated genetic clusters that coincide with known distribution gaps. We provide a more comprehensive description of genetic connectivity in Southwestern Ontario, particularly within Essex County.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The most coherent interpretation of our analyses for Thamnophis butleri is that there are distinct four genetic clusters. The genetic structure that we delineated for Thamnophis butleri supportsNoble et al (2013), who also found geographically delineated genetic clusters that coincide with known distribution gaps. We provide a more comprehensive description of genetic connectivity in Southwestern Ontario, particularly within Essex County.…”
supporting
confidence: 83%
“…We found no compelling evidence that gene flow is impeded by the major rivers that lie along the international border between Canada and the U. (Noble et al 2013;Placyk et al 2012), with no distinction among the groups that colonized this region of postglacial North America. The same is also true for Thamnophis sirtalis sirtalis (Placyk et al 2007) in Ontario and eastern Michigan, and for another co-distributed species,…”
Section: Comparing Population Structure and Genetic Diversity In The Two Gartersnake Speciescontrasting
confidence: 62%
See 1 more Smart Citation